Knowledge and attitudes of pharmacists regarding sugar content in medicine in Bengaluru city: A questionnaire study - Hitendra Ramesh Jain; Vanishree Nanjundaiah; Shivalingeshswamy Hiremath; Chaitra Nagesh; Jeswin Jacob; Keerthi Prasad (Wolters Kluwer Medknow Publications, 2016)
Introduction: Most pediatric medicines are prescribed in a liquid form that includes sugar in the formulation. Accumulating evidence, on a clinical and experimental basis, shows a significant association between the intake of sucrose-based medication and an increased incidence of dental caries. Objective: The aim of this study is to assess the knowledge and attitude of pharmacists regarding sugar content in medicine in Bengaluru city. Materials and Methods: A descriptive, cross-sectional survey was conducted among a sample of the pharmacists in Bengaluru city. A sample of 140 retail pharmacist shops were selected randomly from the total list of retail pharmacist shop registered at the Drug Control Department, Bengaluru. Data regarding their knowledge and attitude in relation to sugar content in medicine was obtained using a questionnaire. Results: Around 67.9% of the pharmacists agreed that sugar-containing medicines taken long-term could lead to dental problems. Only 12.9% of pharmacists believed that patient prefer sugar-free medicine. Most of the pharmacists (72.9%) felt that they themselves have an important role in educating people about sugar containing medicine. Conclusions: Pharmacists requires further knowledge about sugar-free medicine. The expansion of the pharmacist role in oral health promotion would be of value to patients/customers. Various methods should be adopted to increase pharmacist knowledge about dental health.